Suitability study on chicken dung and fruit waste as Black Soldier Fly Larvae (BSFL) diet - Awang, Zarizi; Shahrol Azmi, Siti Azwaadiah; Hashim, Nor Haslina; Hamidon, Nuramidah (Penerbit UTHM, 2020)
Production of chicken increases due to the demand of their eggs and meats [1]. As a result, a massive amount of chicken dung has been generated. Raw chicken dung has adverse effect on plants. Therefore, it should be composted or aged prior to use as raw chicken dung as it contains pathogens as well as urine, feathers, undigested food and coop bedding material that can harm people and animals [2]. If composting is properly done, the process destroys disease-causing organisms, making chicken dung safe to be used around plants, people and pets [2]. Chicken dung is rich in nitrogen, potassium, phosphorus and calcium, and also rich in organic matter compared to other manures. The addition of organic matter to soils increases water-holding capacity of soil, improves aeration and drainage, reduces erosion, reduces fertilizer leaching and improves soil structure for plants [2]. Furthermore, organic matter provides food source for soil microbes, which increases soil biological diversity, accelerates the breakdown of organic nutrients for plants to improve plant health..